2017
DOI: 10.1186/s13054-017-1788-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of altered haemostasis in an ovine model of venovenous extracorporeal membrane oxygenation support

Abstract: BackgroundExtracorporeal membrane oxygenation (ECMO) is a life-saving modality used in the management of cardiopulmonary failure that is refractory to conventional medical and surgical therapies. The major problems clinicians face are bleeding and clotting, which can occur simultaneously. To discern the impact of pulmonary injury and ECMO on the host’s haemostatic response, we developed an ovine model of smoke-induced acute lung injury (S-ALI) and ECMO. The aims of this study were to determine if the ECMO circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…These include the coagulation factors of the contact activation pathway—high molecular weight kininogen (HMWK) and factor XII–as well as high-density lipoprotein (HDL), albumin, immunoglobin G (IgG), and complement component C3 (14). It has been shown by Passmore et al that fibrinogen levels fall in an ovine lung injury model with the commencement of the ECMO circuit and recover to the baseline level within 48 h in keeping with its adhesion to the biosurface and loss from circulation (15). We have also observed this acquired hypofibrinogenaemia in pediatrics following CPB with increased hemorrhage and reduced clot strength (16).…”
Section: Initial Interactions Between Coagulation Factor and Extracormentioning
confidence: 99%
See 1 more Smart Citation
“…These include the coagulation factors of the contact activation pathway—high molecular weight kininogen (HMWK) and factor XII–as well as high-density lipoprotein (HDL), albumin, immunoglobin G (IgG), and complement component C3 (14). It has been shown by Passmore et al that fibrinogen levels fall in an ovine lung injury model with the commencement of the ECMO circuit and recover to the baseline level within 48 h in keeping with its adhesion to the biosurface and loss from circulation (15). We have also observed this acquired hypofibrinogenaemia in pediatrics following CPB with increased hemorrhage and reduced clot strength (16).…”
Section: Initial Interactions Between Coagulation Factor and Extracormentioning
confidence: 99%
“…Factor VIII is an acute phase molecule that is significantly elevated in pro-inflammatory states. Passmore et al showed that FVIII falls in both a lung-injury model and control-animal models on ECMO circuits than those without after 24 h by over 50% (15). This was concurrently noted to be with lower fibrinogen and von Willebrand factor (VWF) levels suggestive of increased consumption of FVIII or decreased VWF-binding ability.…”
Section: Activation Of the Coagulation Cascade In Extracorporeal Circmentioning
confidence: 99%
“…77 However, the etiology of hypofibrinogenemia can be multifactorial, such as dilutional effect due to large extracorporeal volume requiring saline or red cell prime, underlying conditions such as sepsis and liver failure, increased consumption due to thrombosis, disseminated intravascular coagulation (DIC), and hyperfibrinolysis. 78,79 Whole blood testing with viscoelastic hemostatic assays (ROTEM or TEG) can be used in identifying severe hyperfibrinolysis. 80 The mechanism of fibrinolysis in ECMO patients is not very clear and probably involves multiple mechanisms, one being secondary fibrinolysis, in which the production of thrombin stimulates release of tPA from endothelial cells.…”
Section: Acquired Von Willebrand Syndromementioning
confidence: 99%
“…Another study proved in an ovine model that the ECMO therapy increases collagen-induced platelet aggregation, decreases factor VIII and von Willebrand factor; then it defines a decrease of fibrinogen levels and an alteration function in the first 24 hours (29).…”
Section: Pre-clinical Ecmo Studies and Complicationsmentioning
confidence: 99%
“…Due to the critical state of patients suited for its use and the extracorporeal circuit itself, ECMO carries several possible complications that can have a relevant impact on the immediate and remote outcomes. A correct prevention and [39] 848 [29] ECLS, extracorporeal life support; ECPR, ECLS to support cardiopulmonary resuscitation. an early recognition of specific signs can help to reduce the incidence of adverse events (23,35,36) ( Figure 2).…”
Section: Complications During Va-ecmo Supportmentioning
confidence: 99%